Analisis Maqashid al-Syariah Terhadap Pelaksanaan Corporate Social Responsibility (CSR) di PT Bank BRI Syariah Pusat - Aan Finarti Sukandi; Purnama Putra (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2014)
Corporate Social Responsibility is an obligation of a company. BRI Syariah as one of Islamic Financial Institution carries out the social responsibility program.This research aims at finding out the implementation of CSR program at BRISyariah using the perspective of Maqashidsyariah. Based on the categorization and qualification, the indicators measurement which get along with sharia principles are finally invented.The research was conducted at the unit of CSR of BRISyariah head office so that the data cover all of thr implementation of CSR BRISyariah all over Indonesia. The method used was mixed methods research. The quantitative method was used for measuring the CSR program of BRISyariah which was categorized in the component of maqoshidsyariah and qualitative method was used for processing the data from the interview, observation, and literary review proposed to the manager of CSR BRISyariah. The result of the research indicates that the implementation of CSR at BRISyariah is relevant with al maqashidasysyariah. It is proven in thefive main components of maqashid al syariah, which are 1) the protection of the Faith/religion, 2) the protection of life/human soul, 3) the protection of mind /intellect, 4) the protection of wealth, 5) The protection of lineage. While based on the measurement of maqashid al syariah to the CSR at BRISyariah it is known that the indicators of program according to maqashid syariah was the protection of human soul in 2012 with the total number of 30 activities spending 941.305.000 rupiah. The percentageof funding fistribution of CSR was 46% and in 2013 there were 52 activities with the total funding of 985.870.000, the percentage of funding distribution was 50 %.